2008
DOI: 10.1029/2008gl033397
|View full text |Cite
|
Sign up to set email alerts
|

Observational evidence on the stability of the hydro‐glaciological regime of subglacial Lake Vostok

Abstract: Combined geodetic, geophysical and glaciological in situ measurements are interpreted regarding surface height changes over subglacial Lake Vostok and the local mass balance of the ice sheet at Vostok station. Repeated GPS observations spanning 5 years and long‐term surface accumulation data show that the height of the lake surface has not changed over the observation period. The application of the mass conservation equation to purely observational data yields an ice mass balance for Vostok station close to eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 25 publications
12
49
0
Order By: Relevance
“…It confirms our results in Sect. 2.5 and those of previous studies (Richter et al, 2008(Richter et al, , 2014a. It also justifies the assumption of a stable surface made by Ewert et al (2012) as a precondition for the campaign bias determination.…”
Section: Icesatsupporting
confidence: 55%
See 3 more Smart Citations
“…It confirms our results in Sect. 2.5 and those of previous studies (Richter et al, 2008(Richter et al, , 2014a. It also justifies the assumption of a stable surface made by Ewert et al (2012) as a precondition for the campaign bias determination.…”
Section: Icesatsupporting
confidence: 55%
“…The first type are observations performed on lightweight snowmobiles. With the help of such profiles Richter et al (2014a) have shown that the surface elevation around Vostok Station has been stable over the last decade, confirming the results of permanent GNSS observations (Richter et al, 2008(Richter et al, , 2014a. Such profiles acquired on snowmobiles provide accuracies of only a few centimetres (see also King et al, 2009;Siegfried et al, 2011) and are thus well suited for precise studies on local elevation and elevation changes.…”
Section: Kinematic Gnss Observationssupporting
confidence: 52%
See 2 more Smart Citations
“…It is therefore inappropriate to choose an arbitrary density value to reconstruct the snow build-up rate from published accumulation rates, as exercised by Zwally and others (2015) in their attempt to invalidate the conclusion of a stable surface height from Richter and others (2008). The density value of 0.33 g cm −3 adopted by Richter andothers (2008, 2014) represents the best estimate for the surface snow layer combining the results from numerous snow pits and measurements in the Vostok accumulation stake farm (Ekaykin and others, 2003;personal communication from Ekaykin, 2007). This value was used to derive the accumulation rate of 22.9 ± 1.8 mm a −1 from the snow buildup observed in the Vostok stake farm in the period 1970-1995(Ekaykin and others, 2004, and there is neither reason nor evidence given by Zwally and others (2015) for why a density of 0.30 g cm −3 is 'a better value' for the Vostok station area.…”
mentioning
confidence: 99%